KEKUATAN KARAKTER DAN KEBAJIKAN DALAM BIMBINGAN DAN KONSELING - Cucu Arumsari (Journal of Innovative Counseling : Theory, Practice, and Research, 2018)
The strength of character and virtue become an important goal for individual personal development. The strength of character and virtue influence each other. Virtue can have many different strengths of character, the more a person has the character of every virtue, then the individual can be said to have a good character. In counseling and guidance services also have clear goals to help develop optimally the potential of learners who are characterized, so that in every counseling oriented so that learners can develop the potential that exists in him, succeeded in accordance with his ability and become a happy individual